2019
DOI: 10.1248/cpb.c18-00946
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR to Quantify Mobility in Membranes: Diffusion, Protrusion, and Drug Transport Processes

Abstract: Lipid bilayer membranes are soft, fluid, and dynamic architecture where molecules are constantly moving and thermally fluctuating under physiological conditions. In this review, a strategy to quantify molecular dynamics in membranes is introduced by utilizing solution-state NMR spectroscopy as a versatile, noninvasive technique. The dynamics involves lateral diffusion and protrusion motion, in parallel and vertical direction to the membrane surface. Dynamical behavior of small-sized drugs, chemicals, and pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…, describing the transverse relaxation of lipid-bound protons in bilayers is not linear in time t: Γ(t) = R 2 (t) ⋅ t. As the quantity R 2 (t) depends on time t, it cannot be referred to as a "relaxation rate constant", instead we call it a relaxation rate function. Importantly, the main contribution to the transverse relaxation rate function R 2 (t) ∼ ln t, Equation (31), with the proportionality coefficient strongly orientation dependent, nulling at the magic angle orientation. This logarithmic R 2 (t) behavior is intermediate between the case of unrestricted diffusion, 33,34 where R 2 is a constant (does not depend on time), and the case of fully restricted diffusion proposed by Furman et al, 47 where the relaxation was described by a Gaussian-type function, that is, Γ(t) ∼ t 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, describing the transverse relaxation of lipid-bound protons in bilayers is not linear in time t: Γ(t) = R 2 (t) ⋅ t. As the quantity R 2 (t) depends on time t, it cannot be referred to as a "relaxation rate constant", instead we call it a relaxation rate function. Importantly, the main contribution to the transverse relaxation rate function R 2 (t) ∼ ln t, Equation (31), with the proportionality coefficient strongly orientation dependent, nulling at the magic angle orientation. This logarithmic R 2 (t) behavior is intermediate between the case of unrestricted diffusion, 33,34 where R 2 is a constant (does not depend on time), and the case of fully restricted diffusion proposed by Furman et al, 47 where the relaxation was described by a Gaussian-type function, that is, Γ(t) ∼ t 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schoch et al 24 reported D0.810441030.2emμm2false/msec$$ D\sim 0.8\cdot {10}^{-4}-4\cdot {10}^{-3}\kern0.2em {\upmu \mathrm{m}}^2/\mathrm{msec} $$ for supported lipid bilayers and D13103201030.2emμm2false/msec$$ D\sim 13\cdot {10}^{-3}-20\cdot {10}^{-3}\kern0.2em {\upmu \mathrm{m}}^2/\mathrm{msec} $$ for free‐floating bilayers. Quite a few other studies also reported D for model bilayer systems in the range of 1041020.2emμm2false/msec$$ {10}^{-4}-{10}^{-2}\kern0.2em {\upmu \mathrm{m}}^2/\mathrm{msec} $$ (e.g., 25–31 ). Hence, the motion of lipid‐bound protons can be considered as a lateral 2D diffusion, which is accompanied by lipid molecule rotation (Figure 1).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations